The IAFOR International Conference on Education – Hawaii 2021 Official Conference Proceedings 2021
DOI: 10.22492/issn.2189-1036.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Evaluating the e-learning Material for Speaking Practice With the Latest AI Technology

Abstract: Recent years have seen remarkable advancements in information and communication technology (ICT) and artificial intelligence (AI), and many e-learning materials that use ICT and AI have become available on the market. However, none of them has been proven effective at improving speaking skills in English as a Second Language (ESL) and English as a Foreign Language (EFL) classrooms. The author's previous work suggested that speaking practice with voice recognition and an AI scoring system is an effective method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Researchers noted that this type of speaking experience is hard to provide in regular EFL classes due to class size and time constraints within the curriculum. Similarly, an evaluation of a specifically designed EFL chatbot in [23] demonstrated the significant potential of its adaptation. The study found that the chatbot matched students' learning styles and enabled them to learn ubiquitously, thus making them enjoy their learning experience.…”
Section: A Voice-enabled Chatbot For Efl Learningmentioning
confidence: 98%
“…Researchers noted that this type of speaking experience is hard to provide in regular EFL classes due to class size and time constraints within the curriculum. Similarly, an evaluation of a specifically designed EFL chatbot in [23] demonstrated the significant potential of its adaptation. The study found that the chatbot matched students' learning styles and enabled them to learn ubiquitously, thus making them enjoy their learning experience.…”
Section: A Voice-enabled Chatbot For Efl Learningmentioning
confidence: 98%
“…The software's interactive nature motivates and engages learners, leading to better performance in speaking tests and increased levels of interaction and participation [8]. E-learning materials developed using information and communication technology (ICT) were available, but their effectiveness in improving speaking skills in English as a second language (ESL) and EFL contexts was not thoroughly proven [9]. Students have positive perceptions of platforms like Blackboard for learning English.…”
Section: Previous Technology-facilitated Learningmentioning
confidence: 99%